MAQASHID SHARIA’S ANALYSIS OF THE GREEN ECONOMY CONCEPT IN INDONESIA - Miswanto; Tasrif, Muhammad (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
Climate change is a global threat whose impact will be felt by the whole world, including Indonesia in launching a sustainable development program. Every year the forest area in Indonesia decreases by 0.5-1 million hectares. At least in the 2002-2020 period, Indonesia has lost 9.75 million hectares of forest land. Whereas the concept of green economy has long been proclaimed for green economic growth in sustainable development. This research aims to analyze the concept of green economy in the frame of maqashid sharia. This research uses a combined method (triangulation), namely descriptive qualitative research method with verification qualitative design. Data collection techniques through literature review. The results of this study indicate that the concept of green economy in Indonesia in supporting sustainable development is in line with the concept of Islamic economics through maqashid sharia. The concept of low carbon is basically in accordance with protecting the soul, mind and environment. The concept of resource efficient is in accordance with protecting offspring and property. Likewise, the concept of socially inclusive is in the concept of fiqh al-bi’ah (protecting the environment) and the five aspects of preservation in the concept of maqashid sharia.